(untitled) (Journal of Libya for geographical studies, 2022)
The study examines the geopolitical data of the Gulf of Sirte region to determine the impact of these data on the country’s geopolitics highlighted in the geographical vacuum between the two parts of the country most population-focused in the northeast and northwest، the results showed that these data play a prominent role in making the region a geographical separation line between the regions of the country due to market dimensions and geopolitical effects that have had a clear impact when tracking the historical geography of the country in the presence of the bipolar between the two parts of the country in the east and west.